2019
DOI: 10.1002/aoc.5077
|View full text |Cite
|
Sign up to set email alerts
|

Glycine‐functionalized reduced graphene oxide for methylene blue removal

Abstract: Glycine‐functionalized reduced graphene oxide (GRGO) was prepared through the reaction of glycine and chlorine‐functionalized reduced graphene oxide. The product was characterized by SEM, HRTEM, IR, Raman, and XPS. The nitrogen content (8.28%) was high in product, peak at 285.8 eV was assigned to the C–N bond, which implied that the chlorine residues in raw material were substituted by amine group of glycine. The intensity ratio of D and G peak was about 1.5, which also implied that more saturated carbon atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…The highest MB adsorption by N g -CuGA occurred at pH 6 due to the contrasting charges of the adsorbent and adsorbate in this environment, which consequently induce their electrostatic interaction (Fig. 4 a,b) 49 . The negative surface charge of N g -CuGA was confirmed through the pH pzc value; wherein, it was found that the pH pzc of N g -CuGA is 4.73 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The highest MB adsorption by N g -CuGA occurred at pH 6 due to the contrasting charges of the adsorbent and adsorbate in this environment, which consequently induce their electrostatic interaction (Fig. 4 a,b) 49 . The negative surface charge of N g -CuGA was confirmed through the pH pzc value; wherein, it was found that the pH pzc of N g -CuGA is 4.73 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetic model plots fitted the pseudo-secondorder model (Figure 12b) better than the pseudo-first-order model (Figure 12a) as can be confirmed by the higher correlation coefficients (R 2 ) exceeding 0.999. In addition, the calculated qe (cal) values from the pseudo-first-order model ( 93 The experimental data were fitted to four kinetic models, namely pseudo-first and pseudo-second orders, intraparticle diffusion (IPD), and Boyd kinetic models [29,35,57,63,64] (Figure 12), and the obtained parameters of the adsorption kinetics of MB on rGO are summarized in Table 1. The kinetic model plots fitted the pseudo-second-order model (Figure 12b) better than the pseudo-first-order model (Figure 12a) as can be confirmed by the higher correlation coefficients (R 2 ) exceeding 0.999.…”
Section: Adsorptions Kineticsmentioning
confidence: 99%
“…Moreover, the calculated maximum amount of dye per unit weight of adsorbent for complete monolayer coverage (q m ) value was comparable to the experimental values, testifying to the applicability of the Langmuir isotherm model. Compared with other reported graphene-based adsorbents, rGO produced in this study exhibits a qm value (130.2 mg/g) higher than exfoliated GO (17.3 mg/g) [57], rGO-based hydrogel (7.85 mg/g) [11], nanocomposite of β-cyclodextrin/magnetic GO (94 mg/g) [65], interconnected rGO (106.0 mg/g) [66], rGO (121.95 mg/g) synthesized using citric acid [35], glycine-functionalize rGO (117.6 mg/g) [63], suggesting that lemon juice-based rGO is a prominent candidate for removal of organic pollutants.…”
Section: Models and Equationsmentioning
confidence: 99%
“…In addition, when it is used as carrier, few number of functional groups on the rGO will lead to that the interaction between graphene and metal nanoparticles is not strong, which limits their development in the field of catalysis. [ 11‐13 ] In order to solve the above problems and meet the needs of the application, adding other components and modifying different structures on the base of graphene oxide to form a new class of functionalized reduced graphene oxide are much more adaptable for a number of applications. [ 6,14‐16 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…The roles of primary amine or secondary amine groups were used in the formation of graphene‐based materials to improve the performance. [ 13‐15 ] The diamines with two amino groups in its opposite position can react with functional group of GO. As a result, the graphene sheets can be crosslinked by the bifunctional molecules, which are embedded in graphene sheets so as to prevent restacking and aggregation of graphene materials.…”
Section: Background and Originality Contentmentioning
confidence: 99%